Why and when to prefer botulinum toxin injection in childhood strabismus? - Kadriye Erkan-Turan; Hande Taylan-Şekeroğlu; Abdullah Ağın; Ali Şefik Sanaç (The Turkish Journal of Pediatrics)
The aim of this study was to investigate the indications and outcomes of botulinum toxin injection in children with strabismus. The medical records of children who underwent botulinum toxin injection were reviewed. Eighteen patients (13 boys, 5 girls) with a mean age of 9.08±5.93 (6 months to 17 years) years were enrolled in the study. The main indication and diagnosis, initial and final deviation at primary position and the presence of abnormal head position were all evaluated. The most common diagnosis was sixth nerve palsy (7 patients) followed by Duane`s syndrome (4 patients), acquired esotropia (2 patients), acquired exotropia (2 patients), consecutive exotropia (2 patients) and sensory strabismus (1 patient). The leading indications for botulinum toxin injections were the presence of abnormal head position, diplopia and ocular misalignment at primary position. All patients received monocular injection. Fourteen patients had one, 4 patients had more than one injection. The mean follow-up period was 2.78±0.94 months for the first post-injection visit and 21.64±15.23 months for the last visit. Five patients underwent strabismus surgery due to inadequate response to injection. No complication related to injection was observed. Botulinum toxin injection may be preferred in pediatric age group particularly in case of extraocular muscle palsy, diplopia and concomitant deviation either to provide ocular alignment prior to surgery or to prevent the detrimental effect of diplopia on binocularity. The intervention seems to be safe and repeatable in children even though surgery is still inevitable in particular cases.